Fiebernde Geschlechter oder Przybyszewskis Suche nach einer literarischen Sprache über das Begehren - Chołuj, Bożena (Studia Germanica Posnaniensia, 2015)
The main thesis of the article is that Przybyszewski allows his protagonists to suffer by elevated temper-ature or fever to defend them (and their acts) from moral judgement. On the basis of this strategy he becomes free to work out his literary experiments with the aim of finding an adequate language for the description of sexual desire.